INFLUENCE OF TAX-DEFERRED INTEREST BURDEN, THE BURDEN OF TAXES TODAY, AND THE ACCRUAL OF EARNING MANAGEMENT IN DETECTING - Fitra Sutriaji, 07.05.52.0098 Muhammad; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2012)
This research aims to analyze the ability of tax-deferred interest burden and the current tax burden for profit management detection. Profit management gives managers the flexibility to protect themselves and the company in anticipation of events that are unexpected for the benefit of the parties involved.The population in this study is a company manufacturing sectors listed on the Indonesia stock exchange during 2008- 2010. The sample was chosen by purposive technique gained as much as 40 issuers. Logistic regression analysis techniques in this research is used to test the hypothesis.The results of this research show that tax burden now affect the management profit while tax burden-deferred interest accrual and have no effect.Keywords: management, income tax-deferred interest burden, the burden of taxes now, the accrual.